Antara Selfie Dan Selfless: Sebuah Tinjauan Teologis Terhadap Tren Instagram - Yudi Jatmiko (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
The emergence of Instagram has indisputably made the world full of pictures. Messages that are generally dominated by words have turned into a collection of colorful pictures on Instagram. Pictures have brought a world that is beyond words. On the other hand, many experts observe the destructive sides of Instagram. The pictures that are initially meant to reveal beauty have transformed into a means of self-fulfillment. Pictures have turned into a context where the self has become the center of the message and the world. In the Christian faith, this is fatal! A self-centered life is contradictory to the Christian nature as God’s image, which basically must center life on God. The question begs to answer: how should Christian respond to Instagram? This is the focus of the research. To answer the question above, using the methodology of phenomenology approach and literary research, I will explain the history and impacts of Instagram. After that, I will analyze it from the perspective of the Christian faith, especially those that are related to the philosophy undergirding Instagram. Finally, I believe Instagram is not evil per se. However, appropriate responses are needed to bring forth a clearer God’s image in the world that is full of pictures.